A novel application of artificial neural network for recognition of target behind the wall - Singh A.P.; Dwivedi S.; Jain P.K. (My University, 2025)
In this article, a methodology for recognition of an object behind a wall has been proposed. So far research is mainly focused on target detection and localization issue. Very limited work has been reported so far for complete identification (ie, shape and size) of the target. Therefore in this article, a novel Artificial Neural Network based technique is proposed for identification of the targets behind the wall with the through the wall imaging system. For this purpose, an active microwave imaging radar system operating at frequency 3.5-5.5 GHz has been ingeniously designed. An extensive number of experiments were performed while keeping targets made of metal and wood in different shapes and sizes. For identification of the target, an artificial neural network based image reconstruction model has been proposed. From experimental results, it was found that once training of proposed neural network with sample teaching images has been done, it could automatically rectify distortions and reconstruct nearly actual shape and size of the target for test targets. The obtained results are quite satisfactory. © 2019 Wiley Periodicals, Inc.